PENGARUH CASH POSITION, DEBT TO EQUITY RATIO, RETURN ON ASSETS TERHADAP DIVIDEN PAYOUT RATIO (Studi pada Perusahaan Index LQ45 yang terdaftar pada BEI tahun 2014-2016) - Rusmiani, Saripah Dewi (EKONOMIA, 2019)
This study aims to determine the effect: 1) Cash Position to Dividend Payout Ratio; 2) Debt To Equity Ratio to Dividend Payout Ratio; 3) Return On Assets to Dividend Payout Ratio. The data used in this study is secondary data in the form of financial statements of 2014-2016 obtained from the official website of the Indonesia Stock Exchange is www.idx.co.id.The method used in this research is descriptive method. Of the 45 registered company populations in LQ45, 28 samples of firms meeting the test criteria were met. So that the amount of data to be analyzed amounted to 84. Before performing data analysis techniques, first tested the classical assumption. Hypothesis testing using multiple linear regression test with t test and F test with SPSS 23.0 for Windows software.The Partial Calculation Result shows that Cash Position has no significant effect on Dividend Payout Ratio, where the value of t-count <t-table (0.038 <1.990) and probability value (0.969) more than 0.05; Debt To Equity Ratiohas no significant negative effect to Dividend Payout Ratio, where t-count value <t-table (-1.464 <1.990) and probability value (0.147) more than 0.05; Return On Asset has no significant positive effect to Dividend Payout Ratio, where t-count value> t-table (1.022> 1.990) and probability value (0.310) less than 0.05. The result of simultaneous research shows that Cash Position, Debt To Equity Ratio, Return On Asset have positive significant effect to Dividend Payout Ratio, where F-count> F-table or F-count 2,871> F-table2,72